Perbandingan Pemberian Jeruk Manis dan Pisang Ambon terhadap Kadar Hb Ibu Hamil Anemia di Puskesmas Rawat Inap Maja Kabupaten Lebak - Siti Nuriah; Omega DR Tahun (Universitas Malahayati Lampung, 2024)
ABSTRACT Anemia is a nutritional disorder that is often found and is a major nutritional problem in Indonesia. Maja Inpatient Health Center in Lebak Regency in 2021 out of 1,151 pregnant women who experienced anemia, 309 (26.8%) were in the mild anemia category, 305 pregnant women and 4 pregnant women with moderate anemia. One effort to increase Hb levels in anemic pregnant women is by increasing the absorption of iron from foods, such as sweet oranges and Ambon bananas. Knowing the comparison of giving sweet oranges and Ambon bananas to Hb levels of anemic pregnant women at the Maja Inpatient Health Center, Lebak Regency. Quasy experimental design with pretest-posttest design with control group design. The sample is pregnant women who experience anemia in January-February 2023 at the Maja Inpatient Health Center in Lebak Regency as many as 34 samples using a purposive sampling technique. The intervention was given 250g once a day for 7 days. Bivariate analysis used paired simple t test and independent t test. The results of the univariate study mean that the Hb level of anemic pregnant women before administration of Sweet Oranges was 9.835 gr/dl and after 11.224 gr/dl. The average Hb level of anemic pregnant women before administration of Ambon banana was 9,900 gr/dl and after 12,082 gr/dl. The bivariate results of the paired simple t test were 0.000 and the independent t test obtained a p value = 0.000. There are differences in Hb levels of anemic pregnant women between sweet oranges and Ambon bananas. Pregnant women are expected to be diligent in consuming foods that contain iron, one of which is Ambon bananas and sweet oranges so that they can increase Hb levels in the mother's blood, while the process of eating them apart from making juice can also be eaten directly. Keywords: Ambon Bananas, Sweet Oranges, Hb Levels in Anemia Pregnant Women ABSTRAK Anemia merupakan salah satu penyakit gangguan gizi yang masih sering ditemukan dan merupakan masalah gizi utama di Indonesia. Puskesmas Rawat Inap Maja Kabupaten Lebak pada tahun 2021 dari 1.151 ibu hamil yang mengalami anemia sebanyak 309 (26,8%) dengan kategori anemia ringan sebanyak 305 ibu hamil dan anemia sedang sebanyak 4 ibu hamil. Salah satu upaya untuk meningkatkan kadar Hb ibu hamil anemia dengan meningkatkan penyerapan zat besi dari makanan, seperti jeruk manis dan pisang ambon. Mengetahui perbandingan pemberian jeruk manis dan pisang ambon terhadap kadar Hb ibu hamil anemia di Puskesmas Rawat Inap Maja Kabupaten Lebak. Quasy eksperimental desain dengan rancangan pretest-posttest with control group design. Sampel adalah ibu hamil yang mengalami anemia pada bulan Januari-Pebruari tahun 2023 di Puskesmas Rawat Inap Maja Kabupaten Lebak sebanyak 34 sampel dengan teknik purposive sampling. Intervensi diberikan 1 x sehari 250g selama 7 hari. Analisis bivariat menggunakan uji paired simple t test dan t test independent. Hasil penelitian univariat rata-rata kadar Hb ibu hamil anemia sebelum pemberian Jeruk Manis 9,835 gr/dl dan sesudah 11,224 gr/dl. Rata-rata kadar Hb ibu hamil anemia sebelum pemberian pisang ambon 9,900 gr/dl dan sesudah 12,082 gr/dl. Hasil penelitian bivariat uji paired simple t test sebesar 0,000 dan uji t test independent didapatkan nilai p value = 0,000. Terdapat perbedaan kadar Hb ibu hamil anemia antara pemberian jeruk manis dan pisang ambon. Ibu hamil diharapkan rajin mengkonsumsi makanan yang mengandung zat besi salah satunya buah pisang ambon dan jeruk manis agar dapat meningkatkan kadar Hb dalam darah ibu, adapun proses memakannya selain dibuat jus juga boleh dimakan langsung. Kata Kunci: Pisang Ambon, Jeruk Manis, Kadar Hb Ibu Hamil Anemia